Motives of Chinese foreign direct investment in Africa: With regulation effects of institutional quality - Lilin Yuan; Peng Ji (PLoS ONE, 2025)
This article analyzes the motives of Chinese foreign direct investment (FDI) in Africa and the impact of the institutional quality of the host country for the period between 2003 and 2022 from both static and dynamic perspectives by using the OLS, PPML, and GMM methods. The results show that: China has obvious market-, and efficiency-seeking motives, but weak resource- and strategic asset-seeking motives. There is a tipping point for market- and efficiency-seeking motives. Good institutional quality of the host country (region) facilitates FDI expansion. Investment inertia and factor endowments affect long-term FDI. We also examine the moderating effects of institutional quality and the Belt and Road Initiative (BRI) and found that: the host country’s (region’s) institutional environment optimization makes market size more attractive and labor costs less attractive. The BRI itself has no obvious influence on Chinese investment in Africa, while the impact of market size and labor costs became more significant after 2013. Hence, when selecting investment locations, Chinese enterprises should prioritize the host country’s (region’s) market size, labor costs, and institutional quality. Additionally, they should utilize the moderating effect of institutional quality to mitigate the disadvantages associated with higher labor costs.